2017
DOI: 10.1108/jedt-06-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coefficient of performance and simulation design of an air-source heat pump water heater

Abstract: Purpose The purpose of this study was to build and develop mathematical models correlating ambient conditions and electrical energy to the coefficient of performance (COP) of an air-source heat pump (ASHP) water heater. This study also aimed to design a simulation application to compute the COP under different heating up scenarios, and to calculate the mean significant difference under the specified scenarios by using a statistical method. Design/methodology/approach A data acquisition system was designed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…This study of Song et al simulated the performance of a specific building, the Hebei Electric Power Research Institute main building. Tangwe et al [12] predict the COP of an air-source heat pump for heating domestic hot water by simulations. The relevant input data was taken from experiments where data was recorded from the heat pump cycle and at domestic hot-water generation.…”
Section: Literaturementioning
confidence: 99%
“…This study of Song et al simulated the performance of a specific building, the Hebei Electric Power Research Institute main building. Tangwe et al [12] predict the COP of an air-source heat pump for heating domestic hot water by simulations. The relevant input data was taken from experiments where data was recorded from the heat pump cycle and at domestic hot-water generation.…”
Section: Literaturementioning
confidence: 99%
“…By considering various influencing factors and optimizing the campus's actual situation, the researchers found that the system could save 38.9% of energy consumption and increase the performance coefficient by 2.24 times when the operating strategy was at the optimal state point, without affecting user thermal comfort, providing a reference for the optimized operation parameter setting of heat pump hot water units. Tangwe et al [9] predicted the linear relationship between the COP of air-source heat pump systems and the predictive factors in different hot water usage scenarios using mathematical models and simulation applications. They found that environmental conditions are the main factor contributing to COP, with a weight of five times that of other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Heat pumps have been widely applied in the heating, ventilation, and airconditioning (HVAC) system of buildings, by virtue of their energy efficiency, environmental friendliness, compact structure, and ease of installation [4][5][6][7]. Depending on the type of heat sources, heat pumps can be divided into ground source heat pump (GSHP), air source heat pump (ASHP), and solarpowered heat pump (SPHP) [8][9][10][11][12]. Water source heat pump (WSHP) is the most applied type of GSHP.…”
Section: Introductionmentioning
confidence: 99%